Apophatic theology in phenomenological considerations about art - Krawiec, Andrzej (Hybris, 2020)
In the field of phenomenology philosophers more and more frequently show interest in early Christian thought – including apophatic theology – which, in result, affects the understanding of the role and significance of art. „Invisibility” in art and the manifestation of God through the work of art is a mystery which cannot be satisfactorily explained by traditional philosophical aesthetic models. Negative theology, together with its key apophatic way brings a new perspective of understanding art into contemporary aesthetic debates. Its 'reductive' application can be found especially in the theory of the icon. Paweł Florenski's icon analysis and Jean-Luc Marion's category of the ‘saturated phenomenon’ converge in many points. Henry Duméry’s henological reduction which is complementary to, but at the same time exceeds Edmunda Husserl's reductions, extends the horizon of the 'invisible' dimension of art by the relation the Spirit (intelligibility) makes with Transcendence. In the article I will show the cohesion of contemporary phenomenological thought, early Christian apophatics and the theory of the icon. I will also consider whether an aesthetic and theological framework so structured could be valid and useful as a general philosophical theory of art.